Método de determinação da vida útil estimada de pontes, viadutos e passarelas de concreto - Espirito Santo Junior, Celso Martinho do (2020)
Brazil has a road system composed of a large number of Special Engineering Structures in concrete (bridges, viaducts, and walkways), which present serious problems of degradation in their structures, caused by the lack of a maintenance management plan. We do not know the exact number of Special Engineering Structures that make up this system, nor the real state of conservation of these structures, however, there is a growing demand for interventions in these structures, in order to keep them in proper conditions of use and operation. Considering the fact that there is no database with inspection records and the lack of commitment of the competent agencies to change this reality, in an attempt to collaborate with technical-scientific knowledge, indirectly benefiting civil society, this work addresses this issue. Suggesting the use of a mathematical method, known as Method of Factors (MF), in the determination of the Expected Useful Life (EUL) of Special Engineering Structures, through which one can obtain a better understanding of the real state of conservation of these structures, making it possible to estimate how long these structures will be in useful conditions. Considering that MF is not a very widespread method in our technical-scientific academy, and ends up being scarcely used in Brazil, an attempt was made to create, through the bibliographic review, an explanatory concept for a better application of both the method and its use. After conducting these studies, a methodology for using the method in determining the EUL of Special Engineering Structures was suggested. The methodology consisted in defining the values to be attributed to the Reference Useful Life and the MF, when using the method for determining the EUL of Special Engineering Structures. In the study of the method, four different types of scenarios were simulated, covering several anomalous scenarios, alternating the values attributed to MF and EUL. It is concluded that the results obtained for the EULs varied accordingly to the estimated and expected, being the MF and the EUL responsible for this variability. The effectiveness of the method was proven through its application to the four scenarios, which reproduced situations likely to occur in real structures that are in use and operation.